1993
DOI: 10.1073/pnas.90.19.9191
|View full text |Cite
|
Sign up to set email alerts
|

Altered synaptic plasticity and memory formation in nitric oxide synthase inhibitor-treated rats.

Abstract: Nitric oxide (NO) is a messenger molecule that is produced in the brain from the metabolism of L-arginine to L-citruline. Growing evidence suggests a physiological role for NO in long-term potentiation (LTP). Since LTP is a form of synaptic plasticity thought to be involved in learning and memory, we have tested whether inhibition of endogenous NO production affects memory capacities ofrats. We found that the NO synthase [L-arginine, NADPH:oxygen oxidoreductase (nitric oxide-forming), EC 1.14.13.39] inhibitor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
146
1
4

Year Published

1995
1995
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 300 publications
(155 citation statements)
references
References 37 publications
4
146
1
4
Order By: Relevance
“…regulation of central nervous system blood flow, neurotransmitter release from cholinergic nerve fibres and the functional regulation of organs with nitrergic innervation [32].…”
Section: Physiological Functions Of Nnosmentioning
confidence: 99%
“…regulation of central nervous system blood flow, neurotransmitter release from cholinergic nerve fibres and the functional regulation of organs with nitrergic innervation [32].…”
Section: Physiological Functions Of Nnosmentioning
confidence: 99%
“…Consistent with these cellular studies, inhibition of NOS activity may disrupt learning (refs. [16][17][18][19], but see refs. 20 and 21).…”
mentioning
confidence: 99%
“…In line with this conclusion, previous studies have also demonstrated that odor perception is not altered by NO blockade. Specifically, NO did not impair maternal recognition in the lambs (Kendrick et al 1997), nor did it affect the time adult rats spent investigating the novel juvenile (Bohme et al 1993). As our habituation task serves as a measure of olfactory short-term memory, these results also suggest that this specific type of memory remains intact in NO deficient animals.…”
Section: Odor Discrimination and Olfactory Memory Generalizationmentioning
confidence: 99%